Pengaruh Terapi Progresive Muscle Relaxation Terhadap Penurunan Stres Orang Tua Menghadapi Hospitalisasi Di Ruang Rawat Inap Anak RSUD Raja Ahmad Tabib Tanjungpinang - Rozanawati Rozanawati; Mira Agusthia; Yulianti Wulandari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Hospitalization is a condition where a child is sick and undergoing treatment in a hospital. This condition causes stress for children and parents. Stress in parents can have a negative impact on children because it affects the healing process. This research was carried out to see the effect of PMR therapy on reducing parental stress facing hospitalization in the children's inpatient room at Raja Ahmad Tabib Tanjungpinang Hospital in 2023. The research design is a quasi-experimental pre-test post-test design involving 2 groups, intervention and control group. The independent variable is PMR therapy and the dependent variable is stress level. The population in this study was 36 respondents, namely parents whose children were being treated in the pediatric inpatient room. The results of the analysis in the intervention group using the Paired T Test obtained a significant value of .001 < 0.05, so it could be said that Ho was rejected and Ha was accepted. There is a significant effect of Progressive Muscle Relaxation (PMR) Therapy on reducing the stress of parents facing hospitalization in the children's inpatient room at Raja Ahmad Tabib Hospital, Tanjungpinang. Meanwhile, in the control group, there was an increase in stress in the post-test group.